Features and amenities of school playgrounds: A direct observation study of utilization and physical activity levels outside of school time - Swayampakala Kamala; Maslow Andréa L; Colabianchi Natalie (BMC, 2011)
Abstract Background A significant amount of research has examined whether park or playground availability is associated with physical activity. However, little research has examined whether specific features or amenities of parks or playgrounds, such as the number of unique types of playground equipment or the safety of the equipment is associated with utilization of the facility or physical activity levels while at the facility. There are no studies that use direct observation and a detailed park assessment to examine these associations. Methods Twenty urban schoolyards in the Midwest, ten of which were renovated, were included in this study. Using a detailed environmental assessment tool (i.e., Environmental Assessment of Public Recreation Spaces), information on a variety of playground attributes was collected. Using direct observation (i.e., System for Observing Play and Leisure Activity in Youth), the number of adults, girls and boys attending each schoolyard and their physical activity levels were recorded. Each schoolyard was observed ten times for 90 minutes each time outside of school hours. Clustered multivariable negative binomial regressions and linear regressions were completed to examine the association between playground attributes and utilization of the schoolyard and the proportion active on the playground, respectively. Effect modification by renovation status was also examined. Results At renovated schoolyards, the total number of play features was significantly associated with greater utilization in adults and girls; overall cleanliness was significantly associated with less utilization in girls and boys; and coverage/shade for resting features was significantly associated with greater utilization in adults and boys. At unrenovated schoolyards, overall safety was significantly associated with greater utilization in boys. No playground attribute was associated with the proportion active on the playground after adjusting for all other significant playground attributes. Conclusions Having a large quantity of play features and shade at renovated playgrounds were positively associated with utilization of the schoolyard. Modifying playgrounds to have these features may increase the utilization of these facilities outside of school time. Additional research should explore what features and amenities are associated with increased physical activity levels of children and adults who utilize the facilities.